Merancang Model dan Media Pembelajaran - Mawardi Mawardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
The indicator of a professional teachers is the extent to which the teachers has the ability to design instructional well. A good instructional design will effectively achieve the instructional objectives that have been set. The problem that arises is that there is a signal that the teachers implement the learning without first doing systematic instructional design. This paper aims to provide guidance on how instructional components are designed. The instructional components include instructional objectives, materials, model / strategy / method, instructional media and instructional evaluation. The model of instructional component design is using system approach such as Dick model, Carey and Carey. The use of Dick, Carey and Carey model will produce frame of instructional objectives, materials, model / strategy / method, media, and instructional evaluation as needed. Among five components of learning above, the model components and media need to get serious attention because they follow the technology trend. Thus, it needs the signs for choosing and designing the model and the media. The lecturers' view of the process of how the learning act takes place will have implications for the choice of model and the media / delivery technology of the material to be applied. There are two extremes of extreme views about the epistemology of knowledge and the way in which a student's knowledge is acquired, although both are connected through the polar opposite continuum. The two views are: a) an objectivistic view (direct instruction) that is influenced by behavioristic learning theory and cognitive theory, especially information processing theory; b) constructivist views.